Utility of Ultrasonography for Diagnosing and Differentiating Periapical Granuloma from Radicular Cyst - Jia, Wang; Jing, Huang; Xia, Gong; Angang, Ding; Wei, Zhou; Pengfei, Zhang; Shujun, Ran; Mengying, Mao; Zhengwei, Huang; Shensheng, Gu (Academic radiology, 2023)
This study aimed to investigate the reliability and accuracy of high-resolution ultrasonography (US) for diagnosing periapical lesions and differentiating radicular cysts from granulomas. This study included 109 teeth with periapical lesions of endodontic origin from 109 patients scheduled for apical microsurgery. Ultrasonic outcomes were analyzed and categorized after thorough clinical and radiographic examinations using US. B-mode US images reflected the echotexture, echogenicity, and lesion margin, while color Doppler US assessed the presence and features of blood flow of interested areas. Pathological tissue samples were obtained during apical microsurgery and subjected to histopathological examination. Fleiss' κ was used to measure interobserver reliability. Statistical analyses were performed to assess the diagnostic validity and the overall agreement between US and histological findings. The reliability of US compared to histopathological examinations was assessed based on Cohen's κ. The percent accuracy of US for diagnosing cysts, granulomas, and cysts with infection based on histopathological findings was 89.9%, 89.0%, and 97.2%, respectively. The sensitivity of US diagnoses was 95.1% for cysts, 84.1% for granulomas, and 80.0% for cysts with infection. The specificity of US diagnoses was 86.8% for cysts, 95.7% for granulomas, and 98.1% for cysts with infection. The reliability for US compared to histopathological examinations was good (κ = 0.779). The echotexture characteristics of lesions in US images correlated with their histopathological features. US can provide accurate information on the nature of periapical lesions based on the echotexture of their contents and the presence of vascularity. It can help improve clinical diagnosis and avoid overtreatment of patients with apical periodontitis.